The Productivity of White Shrimp at Intensif Fishpond in Tulang Bawang Lampung - Supono Supono (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
Since its introduction on the beginning of 2000’s the cultures of white shrimp (Litopenaus vannamei) in Indonesia highly developed.   This species which is originated from Central  America has successfully triggered shrimp cultures in Indonesia due to its high productivity.  White shrimp has several advantages such as high survival rate (SR), high density, high disease resistance, low feed conversion ratio (FCR) as well as lower feed cost.  The increase of  worldwide market demand caused shrimp farmers to increase their productivity by means of  increasing initial stock. Objective of this experiment was to study the productivity   of  white  shrimp cultured  intensively including yield,  SR,  FCR,  and average  daily gain (ADG). Method of this research was case study of white shrimp culture in Tulang Bawang, The Province of Lampung. Data were taken from 40 of 0.5 ha-shrimp ponds cultured intensively.  Results showed that the average productivity was  7,615 kg per pond with initial stock of    503,735 postlarvae,  SR of 84%, FCR of 1,4 and ADG of 0,15 gram per day.   Key words: productivity of white shrimp, intensive pond